Overexpression of PLK1 relieved the myocardial ischemia-reperfusion injury of rats through inducing the mitophagy and regulating the p-AMPK/FUNDC1 axis. Issue 1 (1st January 2021) - Mao, Shan; Tian, Shuning; Luo, Xianghong; Zhou, Ming; Cao, Zheng; Li, Ji
ABSTRACT: Myocardial cell injury caused by myocardial ischemia and reperfusion is one of the main causes of the occurrence and development of heart disease. Recent study has shown that inducing mitophagy of cardiomyocytes is a crucial method to alleviate ischemia-reperfusion injury. While, Polo-like kinase 1 (PLK1) can induce the mitophagy of breast cancer cells. Moreover, PLK1 was able to promote the expression of p-AMPK and FUNDC1, which are the protective factors for myocardium. Therefore, the mouse model of ischemia/reperfusion was established and the effect of PLK1 on ischemia reperfusion induced myocardial damage was investigated. The PLK1 was overexpressed in H9c2 cells and rat model of ischemia/reperfusion. Ischemia reperfusion inhibited the expression of PLK1. While overexpression of PLK1 relieved the myocardial infarction and myocardium apoptosis through inducing mitophagy in rats model of ischemia reperfusion. In vitro, the H9c2 cells overexpressing the PLK1 were treated with the hypoxia and reoxygenation and the apoptosis, survival rate and expression of mitophagy-related proteins of H9c2 cells were detected using the flow cytometry, CCK-8 assay and western blotting. The results reveled that overexpression of PLK1 alleviated the hypoxia and reoxygenation induced apoptosis of H9c2 cells and promoted the expression of mitophagy-related proteins. In addition, enhanced PLK1 expression promoted the expression of p-AMPK and FUNDC1 in H9c2 cells. However, the inhibition of FUNDC1 abolished the positive effect of PLK1 on H9c2 cells mentioned above. In conclusion, PLK1 alleviated the ischemia reperfusion induced myocardial damage by inducing the mitophagy in a p-AMPK/FUNDC1 signaling dependent pathway. Graphical Abstract: uf0001